If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6y + 2(-1y + 8) = 88 Reorder the terms: -6y + 2(8 + -1y) = 88 -6y + (8 * 2 + -1y * 2) = 88 -6y + (16 + -2y) = 88 Reorder the terms: 16 + -6y + -2y = 88 Combine like terms: -6y + -2y = -8y 16 + -8y = 88 Solving 16 + -8y = 88 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-16' to each side of the equation. 16 + -16 + -8y = 88 + -16 Combine like terms: 16 + -16 = 0 0 + -8y = 88 + -16 -8y = 88 + -16 Combine like terms: 88 + -16 = 72 -8y = 72 Divide each side by '-8'. y = -9 Simplifying y = -9
| t=-10+2t | | 3(x+2)=-(15x+48) | | k-19=-11 | | 2v^3+7v^2+5v= | | -x-1=4 | | -10+5b=10+7b | | x^3-1/4x^5 | | 4x^2+4x=21 | | 4y=5y-9 | | 0.4(b+4)=6 | | 6c-3=7+7c | | -6p=-5p+8 | | 4b-6=2b-8 | | 2h+8=h | | -10q=-8q-6 | | -4(7x-9)+2=-28x+38 | | -5-10z=-9z | | -13+a=0.4 | | 14x^10-8=6 | | n^2-8n=15 | | 8x+1=8(x-1) | | 0.285(4+c)=6 | | 20x-9-16x+2=18x-6-14x+12 | | 1/1/1 | | x-1=-5x-2 | | -4.9=b+6.5 | | 3/3t=1 | | -1(16t(t)-63t-4)=h | | (48x^3)/(30x^2-12x) | | 6u+12=6 | | 5g=105 | | 6(6x+3)=36x+18 |